Laser gas assisted texturing of alumina surfaces and effects of environmental dry mud solution on surface characteristics. Issue 1 (January 2016) - Yilbas, B.S.; Ali, H.; Khaled, M.; Al-Aqeeli, N.; Al-Sulaiman, F.
Abstract: High pressure nitrogen gas assisted laser texturing of alumina surface is carried out and the effects of dust accumulation and mud formation on the surface characteristics are examined. The dust accumulation and mud formation is simulated in the laboratory environments in line with the local environmental conditions. Morphological and metallurgical changes in the laser treated region are examined using scanning electron and atomic force microscopes, energy dispersive spectroscopy, and X-ray diffraction. Surface microhardness is measured and residual stress formed in the surface region is determined from the X-ray diffraction data. Surface hydrophobicity is assessed through the contact angle measurements. Scratch tests are incorporated to measure the friction coefficient of the laser treated and as received workpiece surfaces. It is found that laser texturing results in superhyrophobic surface and the formation of AlN compounds at the textured surface lowers the surface energy while contributing to the surface hydrophobicity enhancement. The mud solution modifies the surface texture characteristics of the laser treated workpieces; in which case, surface hydrophobicity reduces significantly. Surface hardness increases considerably after the laser treatment process because of grain refinement under high cooling rates and volume shrinkage due to AlN compound formation in the surface region. Residual stress is compressive in the surface region of the laser textured workpiece and the mud solution increases slightly surface hardness and residual stress in the surface region.